Imaging of anorectal malformations in utero. Issue 125 (April 2020) - Rohrer, L.; Vial, Y.; Hanquinet, S; Tenisch, E.; Alamo, L.
Highlights: To describe the normal fetal rectum and anal region on US and MRI studies. To describe the prenatal imaging findings suggestive of anorectal malformations. To show examples of confirmed cases of ano-rectal malformations. Abstract: Purpose: To document the imaging findings suggestive of anorectal malformation (ARMs) on prenatal US and MRI. Methods: Retrospective evaluation of the screening US and prenatal MRI exams of the rectum and ano-perineal region in normal fetuses and in patients with ARMs. Results: Examples showing the normal rectal and anoperineal anatomy on prenatal US and MRI exams and the imaging findings observed in different types of confirmed ARMS. Conclusions: Prenatal diagnosis of ARMs requires both a systematic evaluation of the fetal pelvis and perineum and an appropriate knowledge of its suggestive imaging findings.